2018
DOI: 10.3389/fnmol.2018.00260
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing BDNF Transcript Usage During Sound-Induced Memory Linked Plasticity

Abstract: Activity-dependent BDNF (brain-derived neurotrophic factor) expression is hypothesized to be a cue for the context-specificity of memory formation. So far, activity-dependent BDNF cannot be explicitly monitored independently of basal BDNF levels. We used the BLEV (BDNF-live-exon-visualization) reporter mouse to specifically detect activity-dependent usage of Bdnf exon-IV and -VI promoters through bi-cistronic co-expression of CFP and YFP, respectively. Enriching acoustic stimuli led to improved peripheral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(73 citation statements)
references
References 122 publications
(177 reference statements)
0
71
1
1
Order By: Relevance
“…We also observed that central auditory compensation after acoustic trauma-induced cochlear deafferentation was linked to increased hippocampal long-term potentiation (LTP), and recruitment of activity-dependent Bdnf exon-IV and -VI transcription [ 24 ], providing a mechanistic explanation for the idea that temporal auditory processing abilities are related to each individual’s cognitive skills [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that central auditory compensation after acoustic trauma-induced cochlear deafferentation was linked to increased hippocampal long-term potentiation (LTP), and recruitment of activity-dependent Bdnf exon-IV and -VI transcription [ 24 ], providing a mechanistic explanation for the idea that temporal auditory processing abilities are related to each individual’s cognitive skills [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we conclude that a decrease in BNDF levels in the hippocampus of rats submitted to one minute of high-intensity sound, impairs the expression of LTP in the Schaffer-CA1 synapse. Interestingly, Matt et al, (2018) found that prolonged exposure to traumatic noise (120 dB, 6 hours per day for 21 days) in anesthetized rats did not alter LTP and BDNF expression. This suggests that the anesthesia or the prolonged sound exposure protocol might change the hippocampal response to high-intensity sound.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, daily exposure to music at moderated intensity levels (60 dB, 6 hours per day for 21 days) enhanced learning performance and increased BDNF expression in the hippocampus (Angelucci et al, 2007). Similarly, exposure to an 80 dB sound at 10 kHz for 40 minutes in anesthetized rats, increased BDNF expression, hippocampal LTP magnitude and improved the performance in the Morris water maze (Matt et al, 2018). It appears that the effect of moderate noise is more related to the type of noise, and it seems to be contradictory depending on the reports.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A aplicação de BDNF em fatias de hipocampo recupera a LTP em fatias de ratos submetidos à hipóxia crônica intermitente, que apresentam um déficit da LTP hipocampal (Xie et al, 2010). Além disso, em animais transfectados para expressão de BDNF com a sequência exon IV e VI e co-expressão fluorescente de CFP e YFP, foi observado que o enriquecimento acústico com 80 dB melhora as respostas auditivas no tronco encefálico, causa potenciação da LTP nas colaterais de Schaffer, melhora o desempenho dos animais no LAM e aumenta a transcrição de BDNF, ao passo que animais submetidos ao trauma acústico de 120 dB não apresentam aumento na transcrição de BDNF e potenciação da LTP, e apresentam piora no desempenho no LAM (Matt et al, 2018).…”
Section: Bdnf Como Modulador Da Ltpunclassified